The Routledge handbook of phenomenology of emotion - Szanto, Thomas; Landweer, Hilge (Routledge, 2020)
"The emotions occupy a fundamental place in philosophy, going back to Aristotle. However, the phenomenology of the emotions has until recently remained a relatively neglected topic. The Routledge Handbook of Phenomenology of Emotion is an outstanding guide and reference source to this important and fascinating topic. Comprising forty-nine chapters by a team of international contributors the Handbook covers the following topics: historical perspectives, including Brentano, Husserl, Sartre, Levinas and Arendt; contemporary debates, including existential feelings, emotion, affectivity, art and morality; self-directed and individual emotions, including happiness, grief, self-esteem and shame; collective emotions, including empathy and sympathy, political emotions and aggressive emotions; borderline cases of emotion, including solidarity, trust, pain, and forgiveness and revenge. Essential reading for students and researchers in philosophy studying phenomenology, ethics and moral psychology and philosophy of psychology, The Routledge Handbook of Phenomenology of Emotion s also suitable for those in related disciplines such as Religion, Sociology and Anthropology"--
Includes bibliographical references and index
Keywords: Gefühl; Phänomenologie